COVID-19 Maternal Prevention Behavior and Future Intention to Vaccinate for Children - Marjan Zakeri; Ekere J. Essien; Sujit S. Sansgiry (MDPI AG, 2023)
Background: During the COVID-19 pandemic, this study aimed to understand how a mother's current COVID-19 prevention behaviors were associated with the mother's future intention to vaccinate their children against COVID-19. Methods: Using a cross-sectional online survey, mothers who had at least one child between 3 and 15 years old were recruited. COVID-19 prevention behaviors evaluated were wearing a mask, appropriate coughing/sneezing, social distancing, staying home, and handwashing. Participants' age, marital status, race, educational level, incidence of COVID-19 infection in the household, healthcare worker in the household, and future intention to vaccinate children were obtained. Results: Among the 595 participants, 38.3% indicated they did not intend to use the COVID-19 vaccine for their children. Participants with no intention for vaccination had lower mean scores on wearing masks (p < 0.0001), social distancing (p < 0.0001), staying home (p < 0.0001), and handwashing (p < 0.05). The incidence of COVID-19 infection in the household was associated with a lower mean score of staying home (p < 0.01). Conclusion: Our findings indicate that most mothers were compliant with the CDC recommended guidelines at the time of the survey. Mothers who indicated high adherence to prevention behaviors had a higher likelihood to consider vaccination for their children. Now that the COVID-19 vaccine is available for children as young as six months, healthcare providers need to be aware of the relationship between current prevention behaviors and future intention to vaccinate. They need to counsel parents appropriately with recommendations for children to keep practicing prevention behaviors.